2010
DOI: 10.1002/mats.201000003
|View full text |Cite
|
Sign up to set email alerts
|

RIS Model of the Helix‐Kink Conformation of Erythro Diisotactic Polynobornene

Abstract: Computer simulations reveal the unique conformation of or erythro diisotactic polynorbornene, a polymer with numerous important applications in microelectronics. While previous simulations suggested that this polymer adopts a helix‐kink morphology, the results presented herein indicate that the reversal of the helix symmetry is the origin of such kinks which cause a transition from a rigid‐rod conformation to a random coil with increasing molecular weight. An RIS model was developed that accurately predicts th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The helical conformation of PNB forms a near-linear chain which lends itself to stacking of polymer chains, especially when the PNB is functionalized with hexafluoroalcohol groups because they extensively hydrogen bond with one another resulting in in-plane orientation of the polymer along the hydrogen-bonded domains. 15 The stacked, linear assembly of the polymer is consistent with the low in-plane CTE (i.e. axial direction of the polymer backbone) because of the limited ability of the carbon-carbon bonds to expand.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…The helical conformation of PNB forms a near-linear chain which lends itself to stacking of polymer chains, especially when the PNB is functionalized with hexafluoroalcohol groups because they extensively hydrogen bond with one another resulting in in-plane orientation of the polymer along the hydrogen-bonded domains. 15 The stacked, linear assembly of the polymer is consistent with the low in-plane CTE (i.e. axial direction of the polymer backbone) because of the limited ability of the carbon-carbon bonds to expand.…”
Section: Resultsmentioning
confidence: 56%
“…The helical backbone is prone to ordered packing of polymer molecules in certain cases, causing dissolution rate to be largely influenced by molecular weight and additives. 15,16 The specific PNB dielectric evaluated in this study is shown in Figure 1. This polymer is a random copolymer of a hexafluoroalcohol norbornene (NBHFA) and tert-butyl ester norbornene (NBTBE).…”
mentioning
confidence: 99%
“…Since PNB polymers have a helical conformation, this molecular weight is not high enough to induce chain-to-chain entanglement, resulting in low toughness values for the polymer. 11,12 The mismatched CTE between the polymer and silicon along with low toughness led to cracking of thick films. Although uses on polymerbased substrates, such as printed circuit boards, would lower the CTE mismatch and cracking, there is interest in improving the mechanical toughness of the chemically amplified, photo-definable polynorbornene.…”
mentioning
confidence: 99%